Distality of Attentional Focus and Its Role in Postural Balance Control - Kupper, Christian; Roemer, Karen; Jusko, Elizabeth; Zentgraf, Karen (Frontiers in Psychology, 2020)
The role of attentional focusing in motor tasks has been highlighted frequently. The “internal - external” dimension has emerged, but also the spatial distance between body and attended location. In two experiments an extended attentional focus paradigm was introduced to investigate distality effects of attentional foci on balance performance. First, the distality of the coordinates of the point of focus was varied between a proximal and distal position on an artificial tool attached to the body. Second, the distance of the displayed effect on the wall was varied between a 2.5m and 5m condition. Subjects were instructed to focus on controlling either a proximal or distal spot on a tool attached to their head, represented by two laser pointers. Subsequently, they needed to visually track their own body-movement effect of one of the laser pointers at a screen while completing various single leg stance tasks. Center of pressure sway was analyzed using a linear method (classic sway variables) as well as a nonlinear method (multiscale entropy). In addition, laser trajectories were videotaped and served as additional performance outcome measure. Experiment 1 revealed differences in balance performance under proximal compared to distal attentional focus conditions. Moreover, experiment 2 yielded differences in balance-related sway measures and laser data between the 2.5m and 5m condition of the visually observable movement effect. In conclusion, varying the distality of the point of focus between proximal and distal impacted balance performance. However, this effect was not consistent across all balance tasks. Relevantly, the distality of the movement effect shows a significant effect on balance plus laser performance with advantages in more distal conditions. This research emphasizes the importance of the spatial distality of movement effects for human behavior.